Relationship of Cephalopods Orders Based on Morphological Characters - Nova Mujiono; Putri Sapira Ibrahim (Universitas Diponegoro, 2022)
Biodiversity is vital in our daily life. As a maritime country, Indonesian waters harbor many valuable animals such as Cephalopoda. Indonesian waters are rich in various species of cephalopods. Several previous studies on Indonesian cephalopods have been published, from the fishery aspect, only a few studies from the biological aspect. Information on their diversity is still scarce. It may because the low rate of knowledge delivery from the expert to the peoples. Specimen collection is the primary source to conduct a systematic study. The present study aims to introduce the knowledge of the morphologically based taxonomy of Cephalopoda. Using the museum specimen in MZB, we made an introduction on how to distinguish the six orders of Cephalopoda. Only good preserved specimens used. Because this study intended to introduce the morphology, the specimens dissected to show the buccal mass and funnel parts. We selected one species as a representative of each known orders. The morphology was photographed using a camera for the large body parts and using a microscope for the small body parts. A phenogram based on the eleven comparative morphologies is constructed. Three main branches were identified. Nautilida was separated because of the presence of external shell and arm without suckers. Two other branches were mainly grouped based on on the number of arms. Nautiloidea is consist of only Nautilida, a group whose bearing external coiled shell and arm without suckers. The other five orders are classified in Coleoidea, a group whose internal reduced shell and arm with suckers.